PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT. ALFAMART KUTA CANE - Muhammad Alapariji; Nasruddin Nasruddin; Muridha Hasan (Jurnal Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of service quality on customer satisfaction at PT Alfamart Kuta Cane. The background of this research is based on the importance of improving service quality as a key factor in building customer satisfaction and loyalty, particularly in the highly competitive modern retail sector. This study employed a quantitative approach using a survey method. The population consisted of all customers who had shopped at Alfamart Kuta Cane, while the sample comprised 100 respondents selected through accidental sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using multiple linear regression, including validity and reliability tests, classical assumption tests, t-test, F-test, and coefficient of determination (R²). The results revealed that service quality simultaneously had a significant effect on customer satisfaction (F = 46.227; p < 0.05) with an R² value of 0.679. Partially, reliability, responsiveness, tangibles, and assurance dimensions had a significant effect on customer satisfaction, while empathy had no significant effect. These findings indicate that reliability and responsiveness are the dominant factors shaping customer satisfaction. This study confirms the relevance of the SERVQUAL model and the Expectation-Confirmation theory in explaining the relationship between service quality and customer satisfaction in the minimarket retail context. The findings are expected to serve as a reference for Alfamart’s management in designing service quality improvement strategies to maintain and enhance customer satisfaction